IMPLEMENTASI BANTUAN STIMULAN PERUMAHAN SWADAYA (BSPS) DI DESA SAMBIGEDE KECAMATAN BINANGUN KABUPATEN BLITAR PROVINSI JAWA TIMUR - Altesa Wahyudiana Setiyarini; Ananta Prathama (Jurnal Penelitian Administrasi Publik, 2019)
The stimulant assistance of the self-supporting house is one of the central government's attempts to reduce the house unlivable into livable. Sambigede village is one of the Blitar districts where the largest quotas of houses are not livable and is earning the number of the biggest load of self-development development services in Blitar. This kind of research is a descriptive qualitative study. The focus of the study was in the four stages of the organization for stimulant assistance by self supporting housing based on technical instructions for the self supporting housing stimulant assistance program No. 07/ SE /Dr/2018. 4 among the intended stages are community preparation, candidates for assistance, assistance use, and reporting. The data collection techniques used in this study are interviews, observation, and documentation.The results of research that is drawn from the public printing stages are known that it is well received and transparent but is not yet consistent with technical directions and rules that apply this can be seen from the implementation of the ground facilitator's entire proposal for aid, Not yet optimal in the effort because the ground facilitator and village device were ineffective and efficient in searching for the recipient, who met the criteria and twice looked for the recipient to meet the quota. Further from the initialization stage of the help recipient being well-received in accordance with technical directions and the applicable and already optimal rules, it can be seen from the PPK speed for checking the will for the relief recipient's proposal and issuing a decree for the relief recipient.In accordance with the technical instructions and established rules that are already optimal, it can be seen from the time that development rewards did not pass the deadline for the quick program of the self supporting housing supply, the end of the budget and, a good coordination between ground facilitator power, aid receiver, and village devices to address the problem. Next, the non-voluntary reporting stage is in accordance with technical guidance, though in responding submission does not pass the year budget end, but in compiling liability reports by field facilitator power.